Anatomizing Civil War : studies in Lucan's epic technique - Dinter, Martin T. (The University of Michigan Press, 2012)
" Imperial Latin epic has seen a renaissance of scholarly interest. This book illuminates the work of the poet Lucan, a contemporary of the emperor Nero. This maverick but socially prominent poet, whom Nero commanded to commit suicide at the age of 26, left an epic poem on the civil war between Caesar and Pompey that epitomizes the exuberance and stylistic experimentation of Neronian culture. This study focuses on Lucan's epic technique and traces his influence through the Middle Ages and the Renaissance. Martin Dinter's newest volume engages with Lucan's use of body imagery, sententiae, Fama (rumor), and open-endedness throughout his civil war epic. Although Lucan's Bellum Civile is frequently decried as a fragmented as well as fragmentary epic, this study demonstrates how Lucan uses devices other than teleology and cohesive narrative structure to bind together the many parts of his epic body. Anatomizing Civil War places at center stage characteristics of Lucan's work that have so far been interpreted as excessive, or as symptoms of an overly rhetorical culture indicating a lack of substance. By demonstrating that they all contribute to Lucan's poetic technique, Martin Dinter shows how they play a fundamental role in shaping and connecting the many episodes of the Bellum Civile that constitute Lucan's epic body. This important volume will be of interest to students of classics and comparative literature as well as literary scholars. All Greek and Latin passages have been translated"--